Malaria in pregnancy: adverse pregnancy outcomes and the future of prevention - Berhe, Anne D.; Doritchamou, Justin Y. A.; Duffy, Patrick E. (Frontiers in Tropical Diseases, 2023)
Malaria in pregnancy (MiP) poses a dangerous health risk to both mothers and their fetuses, causing severe outcomes such as preterm delivery, intrauterine growth restriction, miscarriage, stillbirth, and neonatal and maternal death. Plasmodium falciparum infected erythrocytes sequester in placental intervillous spaces causing placental malaria (PM), eliciting inflammatory responses associated with severe sequelae. Current MiP prevention strategies have improved pregnancy outcomes, but serious morbidity and mortality persist. Vaccines to prevent MiP and PM are under development and are expected to improve pregnancy outcomes. To prepare for safety and efficacy trials of these vaccines, the incidence of adverse pregnancy outcomes including those caused by MiP should be documented at clinical sites. This review summarizes reported key adverse pregnancy outcomes attributable to MiP, providing important baseline context to define measurable safety and efficacy endpoints for malaria vaccine trials in pregnancy.